Issues of overload agriculture product at FAMA Cameron Highlands Pahang / Rozianna Mahmood - Mahmood, Rozianna (2011)
The Federal Agricultural Marketing Authority (FAMA) has been operating since September 1965. FAMA is also known as “Lembaga Pemasaran Pertanian Persekutuan”. The existence of FAMA is to help all farmers in domestic to market their agricultural products to all over the country and international market. However, there is some problem regarding to the overloading of agricultural products in Malaysia. Therefore, the purpose of this report is to help and to recognize the real problem that caused the overload/dumping of agricultural product problem that faced by FAMA and the farmers. This report is also for recognizing the way to resolve and minimize the loss that was faced by farmers. These researches are focuses on dumping cabbages vegetable at Cameron Highlands in year 2009. The price of 1 kg cabbage went down drastically. The effect from the situation is FAMA must take high risk to take/buy all cabbages vegetable from farmers to cover the cost of farmers and this organization faced heavy losses. The information of this report was obtained by the use of secondary data. The findings show that the good cooperation between FAMA and farmer can help to prevent the dumping cabbage vegetable from happen. It also can help to control the supply of approval permit (AP) that was give to import product (cabbage vegetable) and it can help to control the price of cabbage from falling down drastically. Other than that, the farmers must control the cabbage manufacture/produce from overload. It is recommended that FAMA Cameron Highlands and also all farmers should take responsibility and have a good cooperation with each other to make sure that the dumping of cabbages vegetable problem will not happen again and the price can be at safe range